Incision: Memoirs of a body in pain - Bacalando, Eunice Joy R (Animo Repository, 2024)
This collection of essays about my experiences of illnesses, surgery, mental health issues, and healing is framed by the discourse of Rita Charon, M.D., on the power of writing narratives to give order to the chaotic experience of illness and embrace its meaning-making process as part of the journey towards healing. With my personal essays, I traced the notion of the “autobiographical self-as-consciousness-and-body” to that point in time when it took root in my creative nonfiction writing. This collection is also informed by Elaine Scarry’s notion of metaphor as the language of pain, which builds on the concept that physical pain has no object but itself and, therefore, resists language. Thus, in these narratives of illness, I ask myself the question: how do my experiences of pain find the language and their best metaphorical and narrative vehicles? How does my writing about living in and with my female body-in-pain make meaning, not only for myself but also for my readers? This collection also uses Anne Hunsaker Hawkins’s notion of the agency of patients in the kinds of narratives of illness they can write for themselves and others: didactic pathography, offering helpful information about the specific illness; angry pathography, expressing the patient’s sense of frustration and powerlessness; pathography exploring non-medical alternatives to treatment; and ecopathography focusing on the socio-cultural and environmental factors that affect health.